Late Endocrine Effects after Stem Cell Transplant in a Young Girl with Griscelli Syndrome - Shana R. Mencher; William V. Tamborlane; Anisha D. Patel (Case Reports in Pediatrics)
Background. Griscelli syndrome (GS) is a rare disorder characterized by partial albinism and silver hair with alteration in genes necessary for melanin transport. Type 2 GS is fatal due to severe immunodeficiency without curative stem cell transplant (SCT). Late endocrinopathies are quite common in other disorders after SCT. These complications have not been reported in GS. Case Presentation. A 7-year-old female presented for growth failure with a history of GS status post curative SCT and consequently developed graft-versus-host disease (GvHD). She also had a history of eosinophilic enterocolitis, for which she was taking supraphysiologic glucocorticoids for the past year. She presented with severe short stature along with mild hyperthyroxinemia with subsequent diagnosis of Graves’ disease, which was treated with methimazole. GH therapy was commenced due to persistent growth failure, with a robust increase in growth parameters. She started spontaneous puberty; however, initial biochemical evaluation revealed hypergonadotropic hypogonadism with undetectable anti-Mullerian hormone (AMH) consistent with low ovarian reserve and premature ovarian failure. Discussion. Growth failure was multifactorial due to her inflammatory condition and poor weight gain from multiple underlying illnesses, including hyperthyroidism, as well as chronic supraphysiologic glucocorticoid use. Although hypothyroidism is more commonly seen after SCT, rare cases of hyperthyroidism have been reported. In addition to SCTs, GvHD and GS have been associated with autoimmune conditions. It is important to monitor pubertal progression as the majority of those treated with alkylating agents prior to SCT have pubertal and ovarian failure and remain at risk for premature menopause.